LitSpatz: An App for Literary Walks to Promote and Record Primary Students' Text Comprehension, Perspective Taking and Related Skills - Nora Heyne; Maximilian Pfost; Peter Kuntner (European Journal of Geography)
Teaching listening and reading skills including abilities to adopt spatial and affective perspectives of literary figures and to reflect critically on texts regarding one's own world are central goals of primary school education in Germany, Europe, and beyond. However, many primary school students fail to achieve minimum standards in these skills. To support students in developing these skills and to record their current skill levels, the LitSpatz application was developed. It refers to previous findings on children's cognitive and affective-motivational development, approaches of effective reading instruction, and selected approaches of geographical education. Within this app, primary students are offered the opportunity to take part in literary walks through the city of Bamberg (Germany), either on-site or off-site. Therein, a walk-in story is presented auditorily. Furthermore, illustrations or references to authentic locations are displayed to visualize the scenes' settings and cognitively activating and further questions are asked. The study aims to present the app and initial evaluation data from its use in virtual literary walks (off-site) by children (N = 52) in reading classrooms. In particular, students' characteristics and abilities in relation to text comprehension and aspects of perspective taking (spatial and affective perspective taking, transportation, empathic text comprehension) are explored. Additionally, findings show high levels of listening motivation and enjoyment when using the app. Experiences and results from the use of the app are discussed with respect to future steps regarding its use on-site, the evaluation of its impact, and possibilities for implementing further geospatial technologies.